A Study to Assess the Effectiveness of Structured Teaching Program on Knowledge and Practice Regarding Adult Cardio Pulmonary Resuscitation among Road Traffic Police in Nadiad City - Sapan S. Macwan; Virendra Jain (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: The initial few minutes following an emergency are very crucial care provided during thisperiod has direct bearing on the final outcome in an emergency. Cardiopulmonary resuscitation (CPR) is anemergency clinical procedure for the victim of cardiac arrest or, in a few instances, Respiratory arrest.Aim: This study was conducted to assess the effectiveness of structured teaching program on knowledgeand practice regarding adult cardio pulmonary resuscitation among Road traffic police in Nadiad city, IndiaMaterial and Method: A quasi experimental research study design was used to conduct this study at Nadiad,India from January, 2020 to July, 2020, with pre experimental – one group pre-test and post test design.The knowledge Structure questionnaire and practice checklist was developed to assess the knowledge andpractice of adult cardio pulmonary resuscitation among 60 road traffic police.Results: This study revealed that the pre-test knowledge range was 19, mean 14.05, standard deviation was4.18, mean percentage was 56.2 % while the post test knowledge range was 14-29, mean 21.11, standarddeviation was 3.07, and mean percentage was 72.7 %. The outcome of paired t-test knowledge score andstatistical significance based on Paired t-test as follows: The maximum score was 26, mean was 9.73, standarddeviation was 3.85, mean percentage was 37.4% and paired t-test value was 19.56 that hence there exists asignificance effectiveness on level of knowledge before and after administration of adult cardiopulmonaryresuscitation among Road traffic police.